2014
DOI: 10.1177/2158244014553589
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Chaplains in Veteran Suicide Prevention Efforts

Abstract: In 2007, the U.S. Department of Veterans Affairs (VA) initiated an intensive effort aimed at reducing suicidal behavior among Veteran populations (Kemp, 2014). At present, the number of Veterans who die by suicide is estimated at 18 to 22 per day, accounting for approximately 18% of all suicide completions in the United States (Centers for Disease Control and Prevention, 2014;Kemp & Bossarte, 2013). These high rates are thought to be due, at least in part, to the increased incidence of diagnosed mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Feelings of unease, self-condemnation, and distress can quickly surface (47, 58, 67). Currier and colleagues found that exposure to more traumatic MIEs is negatively correlated with a person’s ability to make meaning of trauma (67), be that meaning made of the MIE, the impact of the MIE on meaning systems, or attributions of the MIE (11, 47, 53, 55, 59–61, 65, 67, 58, 73). From a syndrome perspective of MI (53), perceived loss of life meaning has been identified as a core symptom within the spiritual conflict domain (61).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Feelings of unease, self-condemnation, and distress can quickly surface (47, 58, 67). Currier and colleagues found that exposure to more traumatic MIEs is negatively correlated with a person’s ability to make meaning of trauma (67), be that meaning made of the MIE, the impact of the MIE on meaning systems, or attributions of the MIE (11, 47, 53, 55, 59–61, 65, 67, 58, 73). From a syndrome perspective of MI (53), perceived loss of life meaning has been identified as a core symptom within the spiritual conflict domain (61).…”
Section: Resultsmentioning
confidence: 99%
“…This may involve education, modified exposure, self-forgiveness, dialogue with a benevolent moral authority, reparation and forgiveness, (re)connection and (re)engagement with an S/R community, and integration throughout life (1, 11, 74, 76). Spirituality, which is identified as a treatment modality for MI (p. 704) (77), may enhance recovery and healing (11, 40, 46, 54, 55, 58–60, 63, 64, 68, 72, 73, 78).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been growing empirical interest into examining the contribution of chaplains to suicide prevention efforts targeting current and former military personnel (Kopacz et al., ; Nieuwsma et al., ). Chaplains in the VA health care system actively support veteran populations at increased risk of suicide (Kopacz, ).…”
mentioning
confidence: 99%
“…In this case, clinicians and chaplains must work closely together to reframe old understandings of self and incorrect understandings of religion and spirituality into one that continues to reinforce this newfound sense of hope. 38…”
Section: Hope Emergesmentioning
confidence: 99%